Difference between revisions of "009B Sample Final 1, Problem 2"
Jump to navigation
Jump to search
Line 1: | Line 1: | ||
<span class="exam"> We would like to evaluate | <span class="exam"> We would like to evaluate | ||
− | + | ::<math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg).</math> | |
− | + | <span class="exam">(a) Compute <math style="vertical-align: -15px">f(x)=\int_{-1}^{x} \sin(t^2)2t\,dt.</math> | |
− | + | <span class="exam">(b) Find <math style="vertical-align: -5px">f'(x).</math> | |
− | + | <span class="exam">(c) State the Fundamental Theorem of Calculus. | |
− | + | <span class="exam">(d) Use the Fundamental Theorem of Calculus to compute <math style="vertical-align: -15px">\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg)</math> without first computing the integral. | |
− | |||
− | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |How would you integrate <math>\int e^{x^2}2x~dx?</math> | + | |How would you integrate <math>\int e^{x^2}2x~dx?</math> |
|- | |- | ||
| | | | ||
− | + | You could use <math style="vertical-align: -1px">u</math>-substitution. | |
+ | |- | ||
+ | | Let <math style="vertical-align: 0px">u=x^2.</math> Then, <math style="vertical-align: 0px">du=2xdx.</math> | ||
|- | |- | ||
| | | | ||
− | + | So, we get <math style="vertical-align: -14px">\int e^u~du=e^u+C=e^{x^2}+C.</math> | |
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 31: | Line 32: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We proceed using <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=t^2.</math> Then, <math style="vertical-align: 0px">du=2t\,dt.</math> | + | |We proceed using <math style="vertical-align: 0px">u</math>-substitution. |
+ | |- | ||
+ | |Let <math style="vertical-align: 0px">u=t^2.</math> Then, <math style="vertical-align: 0px">du=2t\,dt.</math> | ||
|- | |- | ||
|Since this is a definite integral, we need to change the bounds of integration. | |Since this is a definite integral, we need to change the bounds of integration. | ||
|- | |- | ||
− | |Plugging our values into the equation <math style="vertical-align: -4px">u=t^2,</math> we get <math style="vertical-align: -5px">u_1=(-1)^2=1</math> and <math style="vertical-align: -3px">u_2=x^2.</math> | + | |Plugging our values into the equation <math style="vertical-align: -4px">u=t^2,</math> we get |
+ | |- | ||
+ | | <math style="vertical-align: -5px">u_1=(-1)^2=1</math> and <math style="vertical-align: -3px">u_2=x^2.</math> | ||
|} | |} | ||
Line 44: | Line 49: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
f(x) & = & \displaystyle{\int_{-1}^{x} \sin(t^2)2t~dt}\\ | f(x) & = & \displaystyle{\int_{-1}^{x} \sin(t^2)2t~dt}\\ | ||
&&\\ | &&\\ | ||
Line 61: | Line 66: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |From part (a), we have <math style="vertical-align: -5px">f(x)=-\cos(x^2)+\cos(1).</math> | + | |From part (a), we have <math style="vertical-align: -5px">f(x)=-\cos(x^2)+\cos(1).</math> |
|} | |} | ||
Line 67: | Line 72: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |If we take the derivative, we get <math style="vertical-align: -5px">f'(x)=\sin(x^2)2x,</math> since <math style="vertical-align: -5px">\cos(1)</math> is | + | |If we take the derivative, we get <math style="vertical-align: -5px">f'(x)=\sin(x^2)2x,</math> since <math style="vertical-align: -5px">\cos(1)</math> is a constant. |
|} | |} | ||
Line 77: | Line 82: | ||
|The Fundamental Theorem of Calculus has two parts. | |The Fundamental Theorem of Calculus has two parts. | ||
|- | |- | ||
− | |''' | + | |'''The Fundamental Theorem of Calculus, Part 1''' |
|- | |- | ||
− | | | + | | Let <math>f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt.</math> |
− | |||
|- | |- | ||
− | | | + | | Then, <math style="vertical-align: 0px">F</math> is a differentiable function on <math style="vertical-align: -5px">(a,b)</math> and <math style="vertical-align: -5px">F'(x)=f(x).</math> |
− | |||
|} | |} | ||
Line 89: | Line 92: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |''' | + | |'''The Fundamental Theorem of Calculus, Part 2''' |
|- | |- | ||
− | | | + | | Let <math>f</math> be continuous on <math>[a,b]</math> and let <math style="vertical-align: 0px">F</math> be any antiderivative of <math>f.</math> |
− | |||
|- | |- | ||
− | | | + | | Then, <math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a).</math> |
− | |||
|} | |} | ||
Line 104: | Line 105: | ||
|- | |- | ||
| | | | ||
− | + | <math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t~dt\bigg)\,=\,\sin(x^2)2x.</math> | |
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | '''(a)''' <math>f(x)=-\cos(x^2)+\cos(1)</math> | + | | '''(a)''' <math>f(x)=-\cos(x^2)+\cos(1)</math> |
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
− | |||
|- | |- | ||
− | | | + | | '''(b)''' <math>f'(x)=\sin(x^2)2x</math> |
|- | |- | ||
− | | | + | | '''(c)''' See above |
|- | |- | ||
− | | '''(d)''' <math style="vertical-align: -5px">\sin(x^2)2x</math> | + | | '''(d)''' <math style="vertical-align: -5px">\sin(x^2)2x</math> |
|} | |} | ||
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 08:41, 10 April 2017
We would like to evaluate
(a) Compute
(b) Find
(c) State the Fundamental Theorem of Calculus.
(d) Use the Fundamental Theorem of Calculus to compute without first computing the integral.
Foundations: |
---|
How would you integrate |
You could use -substitution. |
Let Then, |
So, we get |
Solution:
(a)
Step 1: |
---|
We proceed using -substitution. |
Let Then, |
Since this is a definite integral, we need to change the bounds of integration. |
Plugging our values into the equation we get |
and |
Step 2: |
---|
So, we have |
|
(b)
Step 1: |
---|
From part (a), we have |
Step 2: |
---|
If we take the derivative, we get since is a constant. |
(c)
Step 1: |
---|
The Fundamental Theorem of Calculus has two parts. |
The Fundamental Theorem of Calculus, Part 1 |
Let be continuous on and let |
Then, is a differentiable function on and |
Step 2: |
---|
The Fundamental Theorem of Calculus, Part 2 |
Let be continuous on and let be any antiderivative of |
Then, |
(d) |
---|
By the Fundamental Theorem of Calculus, Part 1, |
|
Final Answer: |
---|
(a) |
(b) |
(c) See above |
(d) |